Cuidados em saúde no contexto da Pandemia de Covid-19 :estratégias e desafios a partir das narrativas das trabalhadoras e dos trabalhadores da Atenção Básica à Saúde em um município do interior do Amazonas - Almeida, Diana Andreza Rebouças (2022)
In 2020, the World Health Organization, due to the occurrence and severity of Covid- 19, declared a State of Public Health Emergency of International Importance, and recognized it as Pandemic on March 11, 2020, a fact ratified by the Brazilian government and the state of Amazonas weeks later. The present study assumes the purpose of understanding how the process of health care developed in Primary Health Care in the municipality of Iranduba - State of Amazonas - during the Covid-19 Pandemic took place, from the perspective of the workers who worked in the area. Theoretically, the research is based on Santos, Birmam, Franco and Cecílio, Machado, Pereira and Freitas, Giovanella, Merhy, Schweickardt and Werneck. As for methodology, this is a qualitative research of a collaborative nature, of the documentary and field type. The documentary research was carried out in the Information Department of the Unified Health System, in the e-Gestor AB System, e-SUS, in the electronic sites of the Health Surveillance Foundation of Amazonas - Dr. Rosemary Costa Pinto, of the State Health Secretariat of Amazonas and of the City Hall of Iranduba, among others. The field research was carried out in the Primary Health Care territory of Iranduba. The interlocutors of the research are the Primary Care workers who integrate the urban, rural and riverine teams, linked to the following Health Districts: Urban, Rio Negro and Rio Solimões. For data collection, two workshops using the Goal Oriented Project Planning method and twenty-nine semi-structured interviews guided by a script were carried out between April and September 2022. All interviews and workshops were recorded and transcribed. The data obtained were categorized and systematized based on the thematic content analysis proposed by Bardin (2016), Minayo (2008), with the help of the Program for Qualitative Data Analysis (NVIVO) version 12 - Plus, with the definition of the following categories: a) Strategies used for the reorganization of the work process in the context of the Covid-19 pandemic in the ABS and b) Challenges to the implementation of health care processes: difficulties for comprehensive care in the ABS. The research showed that primary health care workers had to (re)organize their work processes to face the Covid-19 pandemic. Regarding the work processes of Primary Health Care in Iranduba, we identified that they were significant and relevant to the confrontation of the Covid-19 pandemic, since they contributed to minimize-attenuate the serious effects of the health crisis in the region